Staffing Application System In The Development And Supervision Of Employees Based On Information Technology (It) In Order To Good Government At Regional Office In The Ministry Of Justice And Human Rights Of Central Java (Case Study At Regional Office of the Ministry of Justice and Human Rights of Central Java) - Widya Pratiwi Asmara; Sri Kusriyah Kusriyah; Widayati Widayati (Jurnal Daulat Hukum, 2019)
Based on the study it can be concluded that the implementation of and development of application performance appraisal of civil servants is an assessment of the performance is done at the time of the achievement of targets Employee Work is done in a measured by comparing the actual work with the target set by the organization for each employee, so as to achievement of specified targets at the end of the year. Assessment of Civil Servants implementation work in the Regional Office of the Ministry of Justice and Human Rights of Central Java is done through evaluation methods.Barriers that occur in the Regional Office Law and Human Rights Ministry of Central Java in providing performance benefits as stipulated in the Regulation of the Minister of Law and Human Rights No. 22 of 2014 of which the form has not been found job analysis conducted by management office, employees are not willing / able to develop competency yourself , absence of a good methodology in identifying a job, the boss's behavior is supposed to give an example / role model in encouraging and competencies of subordinates, each employer is aware of the importance of creativity, initiative and a sense of each employee into good consideration in determining the types of work. Efforts are being made by increasing the strong desire of every employee in order to work in accordance with the assessments and improving the competence of oneself, in charging SKP by each employee be done routinely every day to get the direct supervision by the employer concerned, giving performance benefits granted optimally to each employee to the maximum, and the determination of the best boss by the Regional Office of the Ministry of Law and Human Rights, Central Java, so the boss can be an example, determine the class position, and provide the maximum performance benefits in accordance with the capabilities of each employee. Giving performance benefits given up to every employee to the maximum, and the determination of the boss of the best by the Regional Office of the Ministry of Law and Human Rights, Central Java, so the boss can be an example, determine the class position, and provide performance benefits to the maximum in accordance with the capabilities of each employee. Giving performance benefits given up to every employee to the maximum, and the determination of the boss of the best by the Regional Office of the Ministry of Law and Human Rights, Central Java, so the boss can be an example, determine the class position, and provide performance benefits to the maximum in accordance with the capabilities of each employee.Keywords: Staffing Application System; Information Technology (IT); Good Government.